The analyzing the role of electric vehicles in urban logistics: A case of China - Yan, Zhu; Ding, Huiping; Chen, Lu (Frontiers in Environmental Science, 2023)
In recent years, the rapid development of electric vehicles has gained widespread attention, and has especially brought new vitality to the fast-growing logistics service industry. Electric vehicles in urban logistics are not only ideal transportation tools but also do not affect the environment. This study thus implements the economic valuation of electric vehicles in urban logistics from the viewpoints of both manufacturers and business users through the investigation of pricing mechanism and discusses the potential for improving policy-making together with the real case in China. The net present value (NPV) approach is used to quantitatively analyze the investment decisions of urban logistics electric vehicles, with government regulation, incentive policy, and carbon emission trading taken into consideration. Our findings provide insights into the decision-making mechanism for commercializing electric vehicles in urban logistics that involves optimizing the government subsidy and transaction price between the manufacturers and business users. The results imply that with rationalized government policy incentives and coordinated transaction price, both manufacturers and business users are expected to achieve their break-even in limited time periods. The carbon cap placed on business users rather than manufacturers would be relatively more conducive to the marketization process.